CMP Aerogels: Ultrahigh‐Surface‐Area Carbon‐Based Monolithic Materials with Superb Sorption Performance. (22nd October 2014) - Du, Ran; Zhang, Na; Xu, Hua; Mao, Nannan; Duan, Wenjie; Wang, Jinying; Zhao, Qiuchen; Liu, Zhongfan; Zhang, Jin
<x xml:space="preserve">Abstract</x> Monolithic conjugated microporous polymer (CMP) aerogels are obtained in an extremely facile way by selection of adequate reaction conditions and a freeze‐drying technique. The aerogels possess an ultrahigh specific surface area and hierarchical interconnected pores, exhibiting superb gas/oil adsorption performance compared with all microporous organic polymers to date. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>